Modern Methods of Forecasting of Consequences of Administrative Decisions - Valery Leonidovich Makarov; Albert Raufovich Bakhtizin (Управленческое консультирование)
In the article, it is adumbrated about new tools for a quantitative assessment of consequences of some administrative decisions having impact on social and economic indexes of the considered territory (municipality, the territorial subject of the Russian Federation or all country).